Determinants of Profit Growth in Conventional Commercial Banks List on the Indonesia Stock Exchange - Hidayati, Siti; Marlina, Marlina (Budapest International Research and Critics University, 2021)
This study aims to find out the effect of the risk profile, profitability, and capital adequacy on profit growth of conventional general banks in Indonesia. The sampling technique used in this study was probability sampling method, namely simple random sampling where the sample was selected at random and has the same opportunity to be sampled. Based on the results of calculations using the Slovin formula, a sample of 38 banks were obtained. The data used in this study uses quantitative data. In conducting the analysis and hypothesis testing, the procedures were carried out using the help of the Microsoft Excel 2019 program and E-Views version 10.0. Based on the results of the study, it is concluded that the risk profile has no effect on profit growth, and profitability and capital Adequacy have a positive effect on Profit Growth in banking companies listed on the Indonesia Stock Exchange for the period 2017 - 2019. The hypothesis relatet to the influence of risk profile on profit growth was not proven. The results of this study can be used by potential investors and banks, that the risk profile does not affect profit growth, while those that affect profit growth are profitability and capital adequacy.